2012
DOI: 10.4414/smw.2012.13705
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness as a biomarker of subclinical atherosclerosis

Abstract: Intima-media thickness of the carotid artery (CIMT) and its increase is associated with several cardiovascular risk factors and manifest cardiovascular diseases. CIMT is suggested to be an important biomarker of subclinical atherosclerosis. CIMT is measured in B-mode ultrasound images of the carotid tree as a typical double line of the arterial wall. CIMT is best visible in the measurement segment of the distal common carotid artery with lowest measurement variability. The measurement is most reliable over a o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
0
21

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 57 publications
4
91
0
21
Order By: Relevance
“…Increased carotid IMT and plaque formation are considered as early signs of atherosclerosis [20]. Increased carotid wall thickness has been shown to be a significant predictor of coronary and cerebrovascular diseases [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Increased carotid IMT and plaque formation are considered as early signs of atherosclerosis [20]. Increased carotid wall thickness has been shown to be a significant predictor of coronary and cerebrovascular diseases [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36] In this study, we used VCAM-1 not as a marker for targeted plaque imaging, but as an inflammation marker in the context of endothelial regeneration after intravascular procedures. The detection of delayed reendothelialization and prolonged endothelial inflammation induced by diet or drug-eluting stents is an acute issue in clinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…26 cIMT reflects pathological changes in the vessel wall that may result from early atherosclerosis and also from aging of the vessel wall. [22][23][24] High MBL may protect from intimalmedial thickening via its beneficial role in vascular clearup processes and tissue turnover. 7 Importantly, cIMT does not reflect the presence of atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated their longitudinal associations with biomarker scores that reflect low-grade inflammation and endothelial dysfunction and with cIMT as a marker of subclinical vascular disease. [22][23][24] Furthermore, we determined their associations with incident CVD and incident CVEs over a 7-year follow-up period. Previous studies suggested that the effects of lectin-pathway activation in CVD could be both beneficial and adverse.…”
mentioning
confidence: 99%